Orobanche weed management in mustard : Opportunities, possibilities and limitations - Parvender Sheoran; SS Punia; Samunder Singh; Dhiraj Singh (Journal of Oilseed Brassica, 2026)
Orobanche, a ‘super sink’ to mustard plant has threatened the farming community to rethink for alternativeoptions as this parasitic weed has become a menace to Indian mustard [Brassica juncea (L.) Czern &Coss.] cultivation in India. This study reports the judicious and precautionary implication of glyphosateapplication for its better efficacy in reducing the parasitic weed infestation while affording tolerance to themustard crop. Foliar sprays of glyphosate twice; first 25 g/ha at 30 DAS and second 50 g/ha at 55-60 DASis quite effective in reducing the weed infestation by inhibiting the further increase in weed seed bank in thesoil and substantially increasing the crop yields